2015
DOI: 10.1289/ehp.1408163
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Phthalate Exposures and Anogenital Distance in Swedish Boys

Abstract: Background: Phthalates are used as plasticizers in soft polyvinyl chloride (PVC) and in a large number of consumer products. Because of reported health risks, diisononyl phthalate (DiNP) has been introduced as a replacement for di(2-ethylhexyl) phthalate (DEHP) in soft PVC. This raises concerns because animal data suggest that DiNP may have antiandrogenic properties similar to those of DEHP. The anogenital distance (AGD)—the distance from the anus to the genitals—has been used to assess reproductive toxicity.O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
149
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 228 publications
(159 citation statements)
references
References 47 publications
5
149
3
2
Order By: Relevance
“…The AGDs measured in girls and boys are similar to those obtained in previous studies of infants of similar ages. 18,19 As in previous studies, a significant correlation between infant AGD and weight and height was found. 20 The strongest associations between male AGD measurements and breastfeeding types were seen for FB (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…The AGDs measured in girls and boys are similar to those obtained in previous studies of infants of similar ages. 18,19 As in previous studies, a significant correlation between infant AGD and weight and height was found. 20 The strongest associations between male AGD measurements and breastfeeding types were seen for FB (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Although some studies have demonstrated an association between pregnancy exposure to phthalates such as DBP and reduced AGD in sons (62,63), more direct studies in vitro (64) or by xenografting (65,66) have shown no effect of DBP/phthalate exposure on steroidogenesis by the fetal human testis. However, our studies were not undertaken to evaluate if DBP exposure is a cause of TDS disorders in humans.…”
Section: )mentioning
confidence: 99%
“…Diisononyl phthalate is a known replacement for DEHP and has also been found to have antiandrogenic properties in utero in rodent models (18,21). In humans, phthalate exposure during pregnancy is associated with a number of infant and child developmental endpoints that are androgen mediated, including reduced anogenital distance (AGD) (22,23), a measure of fetal androgen exposure, and changes in sex-specific behavior (24,25). Few human studies have examined phthalate exposure and androgen concentrations during gestation; prenatal exposure to DEHP has been negatively associated with free testosterone (FT) and total testosterone (TT) concentrations in pregnancy and in umbilical cord blood (26,27).…”
mentioning
confidence: 99%